Combining Digital Nudges In a Charity Context: Increasing Donations or Sense of Manipulation? - Bergram, Kristoffer; Ouaazki, Abdessalam; Berney, Manon; Bezençon, Valéry; Holzer, Adrian (My University, 2024)
With charitable donations moving online, digital nudges can play a role in influencing donation behaviors. While digital nudges can increase online donations, it is unclear how they affect donor behaviors and perceptions in combination. This paper aims to address this open research gap by exploring the effects of several digital nudge combinations (i.e. default, friction, and social norms) on user donation behaviors and investigates users’ ethical concerns (mainly the sense of manipulation). The results of an online factorial experiment with 794 participants show that combining several nudges tends to increase user donations. However, friction is the main driving factor. Furthermore, our results show that nudging users increases their sense of manipulation, which increases their likelihood of regretting their donation. This is an important finding in a charitable giving context, where organizations rely upon a positive user experience to produce recurring donations.
Keywords: Digital nudging; Default; Friction; Social norms; Online charitable giving